Macrostructural Brain Changes in Patients with Longstanding Type 1 Diabetes Mellitus – a Cortical Thickness Analysis Study - Frøkjær, J. B.; Brock, C.; Søfteland, E.; Dimcevski, G.; Gregersen, H.; Simrén, M.; M. Drewes, A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Longstanding diabetes mellitus (DM) is associated with the risk of complications affecting the central nervous system. The aims were to study brain volume and cortical thickness in regional brain areas in DM patients and to correlate the findings with relevant clinical data.15 patients with longstanding (average 24.6 years) type 1 DM and 20 healthy controls were studied in a 3T magnetic resonance scanner. Using an automated surface based cortical segmentation method, cortical thickness was assessed in anatomical regions including total and lobe-wise grey and white matter volumes. Also morphological changes were evaluated.No differences between patients and controls were found in regard to number of white matter lesions (P=0.50), grey and white matter volumes (P=0.25) and overall cortical thickness (P=0.64). Subanalysis revealed exclusively reduced cortical thickness of the postcentral (P=0.03) and superior parietal gyrus (P=0.008) in patients. The cortical thickness of these regions was not associated with diabetes duration, age at diabetes onset or to HbA1c (all P>0.08). Patients with peripheral neuropathy showed reduced right postcentral gyrus cortical thickness compared to patients without peripheral neuropathy (P=0.02).Patients with longstanding type 1 diabetes showed cortical thinning involving sensory related areas, even though no overall macrostructural brain alterations were detected. This could possibly have underlying functional significance since cortical thinning was associated to presence of peripheral neuropathy. The absence of universal macrostructural changes might illustrate that more pronounced brain pathology is likely to be preceded by more subtle microstructural changes as reported in other studies.
Keywords: magnetic resonance imaging; cortical atrophy; diabetes mellitus; neuropathy; CNS complications; nerve damage